Análisis contable en la gestión presupuestaria en el GAD Municipal de Vinces en el período 2019-2020 - Franco Manjarrez, Byron Alexander (2021)
The case study called "Accounting analysis in budget management in the Vinces Municipal GAD in the period 2019-2020". The GADs have been created with the purpose that the citizens and the government administration become easier to manage around each canton of each province of the country, so that there is a hierarchical system for the benefit of the people of a certain area. The budget is an instrument that allows the aforementioned entity to make decisions, meet the objectives of these government institutions for the constant sustainable development of the same and for the improvement of the infrastructure. This work has been structured under the sub-line of research Financial, tax management and social commitment. The financial director was interviewed, who provided information about the state of budget execution, the analytical method was used because it consists of carrying out the respective analysis of agreements for the 2019-2020 periods, determining the degree of compliance with the institutional goals and objectives, it was based the study by means of a descriptive type investigation for the knowledge related to the particular facts of the budget management of the Autonomous Decentralized Municipal Government of the Vinces canton. Percentage variations of the two periods under study were applied, financial indicators were also applied that allowed obtaining general conclusions. On the other hand, the current expenses that are those generated for the development of the activities of the municipal GAD were lower than the income in 2019, but in 2020 the expenses exceeded the income, for which a budget deficit was generated.